Sub-Irrigated Alfalfa Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2004)
This publication contains information for a projected budged reflecting expected income and cost based on sub-irrigated alfalfa production practices in western Kansas.
MF2367_2004_10
Keywords: MF2367; Economics; Crops; MF